Intact ribosomal DNA arrays of Potentilla origin detected in Erythronium nucleus suggest recent eudicot-to-monocot horizontal transfer - Bartha, László; Mandáková, Terezie; Kovařík, Aleš; Bulzu, Paul-Adrian; Rodde, Nathalie; Mahelka, Václav; Lysak, Martin A; Fustier, Margaux-Alison; Šafář, Jan; Cápal, Petr; Keresztes, Lujza; Banciu, Horia L (The New phytologist, 2022)
During our initial phylogenetic study of the monocot genus Erythronium (Liliaceae), we observed peculiar eudicot-type internal transcribed spacer (ITS) sequences in a dataset derived from genomic DNA of Erythronium dens-canis. This raised the possibility of horizontal transfer of a eudicot alien ribosomal DNA (rDNA) into the Erythronium genome. In this work we aimed to support this hypothesis by carrying out genomic, molecular, and cytogenetic analyses. Genome skimming coupled by PacBio HiFi sequencing of a bacterial artificial chromosome clone derived from flow-sorted nuclei was used to characterise the alien 45S rDNA. Integration of alien rDNA in the recipient genome was further proved by Southern blotting and fluorescence in situ hybridization using specific probes. Alien rDNA, nested among Potentilla species in phylogenetic analysis, likely entered the Erythronium lineage in the common ancestor of E. dens-canis and E. caucasicum. Transferred eudicot-type rDNA preserved its tandemly arrayed feature on a single chromosome and was found to be transcribed in the monocot host, albeit much less efficiently than the native counterpart. This study adds a new example to the rarely documented nuclear-to-nuclear jumps of DNA between eudicots and monocots while holding the scientific community continually in suspense about the mode of DNA transfer.
Keywords: Erythronium; horizontal gene transfer; mezerníky ribozomální DNA; liliovité; ribozomální DNA; lateral gene transfer; Potentilla; Liliaceae; rDNA; ribosomal RNA genes; DNA, Ribosomal; hybridizace in situ fluorescenční; DNA, Ribosomal Spacer; Phylogeny; fylogeneze; internal transcribed spacer; In Situ Hybridization, Fluorescence